Choice under uncertainty in developing countries - Glenn W. Harrison; Steven J. Humphrey; Arjan Verschoor (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2005)
We review experimental evidence collected from risky choice experiments using poor subjects in Ethiopia, India and Uganda. Using these data we estimate that just over 50% of our sample behaves in accordance with expected utility theory and that the rest subjectively weight probability according to prospect theory. Our results show that inferences about risk aversion are robust to whichever model we adopt when we estimate each model separately. However, when we allow both models to explain portions of the data simultaneously, we infer risk aversion for subjects behaving according to expected utility theory and risk seeking behavior for subjects behaving according to prospect theory. We conclude that the current practice of designing policies under the assumption that one or other explains all behavior is fundamentally flawed.
Keywords: O12; D01; D81; C93; 330; choice under uncertainty; field experiments; developing countries